A General Profile of Organisational Culture in Family and non-Family Businesses - Dorda, Beskida; ShtÃ«mbari, Eriona (Mediterranean Journal of Social Sciences, 2019)
Companies perform in the market by their unique organisational culture (OC). Literature has shown that OC is a crucial factor for successful businesses. Being such an important element, OC is widely studied and has captured the attention of researchers all over the world. Strategic orientation, tradition or new marketâ€™s demands are main factors that can influence the culture of each enterprise and can provide distinctive organisational cultures. This paper intends to fill a gap in the literature about the general dimensions of organisational culture in Albanian companies. This study also compares results between family and non-family firms. Albania is a developing country that is rapidly changing, and its market is affected by its national culture and globalisation as well. Around 30 years ago a free market was established in Albania. In this perspective, it will be beneficial to develop a comprehensive insight into the culture that business has created during this period of time. Data are gathered between December 2018 and June 2019. SPSS is used to analyse them. Company's fundamental values, attention to details and leaders as a good representation of OC are factors that showed interesting results, indicating a clear perception. Furthermore, regarding the attitudes of family businesses (FBs) compared to non-FBs, innovation and companies' behaviour toward their members are found to have differences.